Medical Decision Support Systems in Africa - Bediang, G.; Bagayoko, C. O.; Geissbuhler, A. (Yearbook of Medical Informatics, 2010)
Objective: To present an overview of the current state of computerbased medical decision support systems in Africa in the areas of public health, patient care, and consumer support.Methods: Scientific and gray literature reviews complemented by expert interviews.Results: Various domains of decision support are developed and deployed in Sub-Saharan Africa: public health information systems, clinical decision-support systems, and patient-centred decisionsupport systems.Conclusions: Until recently, most of these systems have been deployed by international organizations without a real ownership policy entrusted to the African stakeholders. Many of these endeavours have remained or ceased at the experimentation stage. The multiplicity of organizations has led to the deployment of fragmented systems causing serious interoperability problems. In addition to basic infrastructures, these studies also highlight the importance of good organization, training and support, as key to the success and sustainability of these decision support systems.
Keywords: Decision support system; Africa; telemedicine; eHealth; mHealth